(3neSGqQ GdTjYI aj eNJUQ JhGQjN GdTQjYIs - (3eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe GdYcHQqj, CHh YHO Gddg, GdeajO, hjYQa HGHf GdeYde , J (B413 (3g`s
(3ChdgG (B:s
(3HYO GdMeO dg CeG HYO aEfg deG cGf Yde GdJGQjN ef GdYdhe GdJj jfHZj eYQaJgG hjLH eWGdYI cJHgG s
(3BNQgG (B:s
(3hjfHZj ddMGLH Cf dG jHdZ GdQSGdI EdG eG jbGd dg dGjRjO Ydi Pdc hdG jfbU gPG hGddg SHMGfg hJYGdj GYde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B21 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B306s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs